Diversidad genética de las heliconias y su aplicación en fitorremediación, identificación varietal y mercadeo (2022)
Genetic diversity of heliconias and their application in phytoremediation, varietal identification and marketing, has a common thread (the study of genetic diversity and phenotypic expression) and a unifying purpose (contribute to the tropical flower market and metal decontamination strategies heavy). Organized into three chapters, it presents research in areas connected by the exploration of genetic diversity: «Evaluation of gene expression, associated with the tolerance of some heavy metals in Heliconia species»; «Use and development of SSR molecular markers for varietal identification of commercial cultivars of Heliconia in Colombia»; Genetic, cultural and climatic aspects of Colombian heliconias as key factors for a protection brand and commercial strategy. The chapters present research results on three related topics which combine challenges of production.